2016
DOI: 10.1007/s00198-016-3676-6
|View full text |Cite
|
Sign up to set email alerts
|

Teriparatide improves volumetric bone mineral density and fine bone structure in the UIV+1 vertebra, and reduces bone failure type PJK after surgery for adult spinal deformity

Abstract: Prophylactic TP treatment improved the volumetric BMD and fine bone structure at UIV+1 and reduced the PJK-type 2 incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(86 citation statements)
references
References 39 publications
3
81
1
1
Order By: Relevance
“…Thus, caution should be exercised when considering the risk of PJK type fracture in PD patients. Yagi et al reported that teriparatide treatment started immediately after surgery resulted in a decrease in rates of PJK-type bone fracture [25]. If BMD is low, then administration of osteoporotic drugs such as teriparatide could be a viable option to decrease the risk of complications, as suggested in the previous study.…”
Section: Resultsmentioning
confidence: 77%
“…Thus, caution should be exercised when considering the risk of PJK type fracture in PD patients. Yagi et al reported that teriparatide treatment started immediately after surgery resulted in a decrease in rates of PJK-type bone fracture [25]. If BMD is low, then administration of osteoporotic drugs such as teriparatide could be a viable option to decrease the risk of complications, as suggested in the previous study.…”
Section: Resultsmentioning
confidence: 77%
“…Yagi and colleagues reported on the effectiveness of teriparatide as a protective treatment for junctional fracture following ASD surgery in women with osteoporosis or osteopenia. 93 Although their clinical effectiveness remains under investigation, junctional tethers are an emerging technique with potential to reduce PJK risk (Fig. 7).…”
Section: Pseudarthrosis and Instrumentation Failurementioning
confidence: 99%
“…32,36 In the future, more aggressive attention to bone optimization may also reduce junctional fractures. 93 Ongoing advances in junctional tethers may also provide another approach to reduce PJK. 7…”
Section: Advances To Further Reduce Complicationsmentioning
confidence: 99%
“…Bei Osteoporose befürworten die Autoren inzwischen eine aggressive 6-monatige medikamentöse Therapie vor dem elektiven Eingriff. Neben der Gabe von Vitamin D und Calcium hat hier vor allem der Einsatz von Teriparatid, einem rekombinanten humanen Parathyroidhormon (rhPTH), gute Resultate gezeigt [16].…”
Section: Klassifikationunclassified